Guest editorial rapid motorization in asian cities: urban transport infrastructure, spatial development and travel behavior - Kitamura, R.; Mohamad, J. (2009)
Transport infrastructure has played an indispensable role in the growth of urban socities. During the first half of the 20th century transport, particularly rail was seemed as asserting a powerful influence on economic growth and industrial location. The concentration of employment in, or close to, city centers produced radial commuting patterns with traffic flows concentrated along rail, tram bus routes. Changes in the nature of industrial activities or within urban communities are followed by changes in transport requirements. Hence, land use patterns are built environments in turn shape the demand for travel. Because of this inter-dependency, it is important to note that carefully-integrated and coordinated transportation and urban development is essential to ensuring a sustainable future, not only in an environmental sense, but socially and economically as well.